2018
DOI: 10.1016/j.clnu.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caloric intake in critically ill patients with, and without, refeeding syndrome: A retrospective study

Abstract: Refeeding syndrome is common among prolonged mechanically ventilated critically ill patients, however not predictable by baseline characteristics. Among patients that develop refeeding syndrome low caloric intake was associated with a reduction in 6-month mortality risk. This effect was not seen in patients without refeeding syndrome. Findings support caloric restriction in refeeding syndrome during critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
4
28

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 27 publications
5
69
4
28
Order By: Relevance
“…RS was observed in 36.8% of patients, with no statistically significant difference in hospital morbidity, and with a trend toward reduced length of stay, in the lower‐calorie group. They also found that low calorie intake was associated with an increased overall survival at day 180 109 …”
Section: Avoidance Of Refeeding Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…RS was observed in 36.8% of patients, with no statistically significant difference in hospital morbidity, and with a trend toward reduced length of stay, in the lower‐calorie group. They also found that low calorie intake was associated with an increased overall survival at day 180 109 …”
Section: Avoidance Of Refeeding Syndromementioning
confidence: 99%
“…Diseases and Clinical Conditions Associated With anIncreased Risk of Refeeding Syndrome 15,[109][110][111]. …”
mentioning
confidence: 99%
“…Likewise, in patients developing refeeding syndrome after initiation of artificial feeding, nutrient restriction dramatically improved survival . Of note, a recent observational study found that patients developing refeeding syndrome could not be identified in advance, which broadens caution not to advance nutrition too aggressively to all ICU patients …”
Section: Results From Recent Feeding Rctsmentioning
confidence: 99%
“…36 Of note, a recent observational study found that patients developing refeeding syndrome could not be identified in advance, which broadens caution not to advance nutrition too aggressively to all ICU patients. 37 Several experts have attributed the neutral or negative impact of early enhanced feeding in RCTs to the relatively low amount of administered proteins. [38][39][40] However, 1 recent RCT that specifically evaluated a higher vs lower protein dose failed to demonstrate a beneficial impact of a higher protein dose.…”
Section: Results From Recent Feeding Rctsmentioning
confidence: 99%
“…4 Low caloric intake feeding can decrease the 6 month mortality rate by 60% of RFS patients on mechanical ventilators for more than seven days, compared to a high caloric intake group. 13 This is also supported by the systematic review that showed caloric restriction with a protocol can improve mortality and survival time. 7 Regarding the composition of the diet, high carbohydrate intake is more likely to cause RFS in contrast to the low amino acid intake.…”
Section: Caloric Requirementmentioning
confidence: 65%